Autoajuda, trabalho e novas subjetividades em tempos de incerteza: análise do discurso de o monge e o executivo e seja líder de si mesmo - Sá, Danielle Rebouças (2013)
Contemporary society is marked by large and constant changes. We live in a fast, fluid and dynamic world, where the inherited certainties of tradition and first modernity give place to uncertainties, risks and unpredictability. Changes are socioeconomic, technological and cultural involving new forms of individual thinking, feeling, acting, and living. Such changes occur singularly in working life, accompanying the changes in the capitalist production mode. The new stage of post-industrial capitalism produces new ideologies and orders of discourse that strongly challenge subjectivities. These ideologies and orders of discourse are materialized and disseminated through self-help manuals and other hybrid types, which tend to favor certain representations of work, the company and the employee, and also to inculcate certain ways of being and acting inside and outside of the workplace. This research investigated how this type of literature provides resources that claim to enable the individual to cope with the new work configuration nowadays and with the existential dilemmas arising from this new scenario. Assuming here the language as a social practice, our main objective was to investigate how the self-help books are related to the sense of uncertainty that characterize the contemporary experience of work and other spheres of life. For this we use the approach of Critical Discourse Analysis (CDA) in order to identify the main ideological investments of self-help speech, as presented in two books of the genre: The Monk and the executive, James Hunter (2004) and Be the leader of yourself, Augusto Cury (2004). The analysis revealed that the works studied tend to disseminate certain representations of current problems (for example, unstable and precarious work, the difficulties of leadership) problems as personal and subjective nature, the exclusive purview of the individual. Both take issues and social problems to the sphere of interiority, proposing theories about how the mind works and intervention techniques for personal development and for changing behaviors and habits. To represent these problems as issues of interiority and interpersonal relationships, the works tend to blame the person for the solution of such problems and the pursuit and achievement of your success and happiness. In according to a consumer society depoliticized and fragile in criticizing the system and the social and economic macrostructures, the discourse of self-help drive its "critical" to the individual. This individual feels forced to turn to himself and to interfere on their own attitudes, feelings and behaviors to create change and achieve success. The discourse of self-help in this context meets the new demands and requirements of the existing capitalist order: people engaged in constant self-examination and self-regulation and willing to reorganize while facing uncertainty and risk that are part of their lives. The self-help manuals contribute to the formation of new subjectivities and the inculcation of the "new spirit of capitalism", with new ways of being, acting and interacting that adapt to new labor realities and to the capitalist order in force.